Unravelling genetic etiology of cerebral palsy: findings from a Slovenian pediatric cohort - Arkar Silan, Ula; Trebše, Ana; Kovač, Jernej; Rogac, Mihael; Troha Gergeli, Anja; Šket, Robert; Bregant, Tina; Neubauer, David; Peterlin, Borut; Osredkar, Damjan (Frontiers in Neurology, 2025)
IntroductionCerebral palsy (CP) is a permanent movement or postural disorder due to non-progressive injury to the developing brain, with recent research suggesting a genetic contribution in many patients. This study aimed to investigate the genetic etiology of CP in Slovene children without a previously suspected genetic cause or with prior negative genetic testing.MethodsAll children born after 2003 from the Slovenian National Registry of Cerebral Palsy (SRCP) without an established genetic diagnosis were invited to participate in this cross-sectional study. Whole exome sequencing (WES) was conducted, followed by analysis of 110 CP-associated genes. Thirteen patients underwent additional family segregation by Sanger sequencing. Genetic findings were classified according to the ACMG guidelines.ResultsThe study included 136 children, of whom 68 (50%) were male. Spastic CP was identified in 85% of the participants, dyskinetic in 13%, and ataxic in 2%. Gross Motor Function Classification System (GMFCS) levels varied, with the majority (36%) classified as level I. Pathogenic variants, likely pathogenic variants, or ‘de novo’ variants of unknown significance (VUS) were identified in nine children (6.6%) in ATL1, CTNNB1, DYRK1, KMT2A, PROC, SPAST, ZC4H2, and ZSWIM6. Among these nine children, two had normal brain Magnetic Resonance Imaging (MRI) and three had an unsuspicious medical history.ConclusionThis study identified plausible, possible, or definite genetic etiologies in a cohort of children with CP. Apart from the exclusion of individuals with a previously established genetic diagnosis, no other selection criteria were applied, allowing for an inclusive assessment of genetic contributions within this population. With the advent of personalized medicine and genetic treatment, understanding the genetic underpinnings of CP is crucial for targeted therapy.